Community Development Melalui Program Kampung Sejahtera Mandiri (Ksm) Sebagai Sarana Pemberdayaan Perempuan - Siti Nabila (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This research uses a descriptive qualitative approach. Data were collected by means of observation, interviews, and documentation. While the research data analysis stage used in this study includes the stage before in the field, the stage while in the field, and the conclusion stage. The theoretical concept used in this study is the Lubis theory. Consists of 5 dimensions, namely, Advocacy, Community Organizing, Capacity Building, Network Development, and Communication, Information and Education. The results of the research and discussion that the researcher has carried out, and based on the dimensions of the research that are the basis for this research, include the standards and objectives of Advocacy, Community Development, Capacity Building, Network and Communication Development, Information and Education. The supporting factors are the support from across sectors, the tenacity and creativity of women there and the development of technology that has improved. The inhibiting factors in this empowerment are high population but low quality of human resources, low per capita income, community economy is still lacking for product marketing. And Knowledge of technology in product marketing.